2017
DOI: 10.3390/polym9080350
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Nanoclay Particles at the Interface and Their Influence on the Microstructure Development and Rheological Properties of Reactively Processed Biodegradable Polylactide/Poly(butylene succinate) Blend Nanocomposites

Abstract: Abstract:The present work investigates the distribution of nanoclay particles at the interface and their influence on the microstructure development and non-linear rheological properties of reactively processed biodegradable polylactide/poly(butylene succinate) blend nanocomposites. Two types of organoclays, one is more hydrophilic (Cloisite ® 30B (C30B)) and another one is more hydrophobic (Betsopa TM (BET)), were used at different concentrations. Surface and transmission electron microscopies were respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…They found that hydrophobic montmorillonite Cloisite C20A (Montmorillonite modified with dioctadecyl dimethyl ammonium chloride surfactant) and Cloisite C10A (Montmorillonite modified with benzyldimethylhexadecyl ammonium chloride) located at PP/PS interface and caused PS droplet size reductions while hydrophilic clay particles, Cloisite C30B (Montmorillonite modified with methyl tallow bis-2-hydroxyethylammonium) and Cloisite CNa + (Pristine montmorillonite) were found to accumulate inside the PS droplets and had little influences on the morphology of the PP/PS blends. Similar behaviors were found in PLA/PBS blends [33]. Kelnar et al [34] reported that in PA6/EPR blends, clay modified with lower polarity, that is, Cloisite C15A (Montmorillonite modified with dimethyl, dehydrogenated tallow quaternary ammonium ion) and C20A, showed the most significant compatibilizing effect.…”
Section: Introductionsupporting
confidence: 57%
“…They found that hydrophobic montmorillonite Cloisite C20A (Montmorillonite modified with dioctadecyl dimethyl ammonium chloride surfactant) and Cloisite C10A (Montmorillonite modified with benzyldimethylhexadecyl ammonium chloride) located at PP/PS interface and caused PS droplet size reductions while hydrophilic clay particles, Cloisite C30B (Montmorillonite modified with methyl tallow bis-2-hydroxyethylammonium) and Cloisite CNa + (Pristine montmorillonite) were found to accumulate inside the PS droplets and had little influences on the morphology of the PP/PS blends. Similar behaviors were found in PLA/PBS blends [33]. Kelnar et al [34] reported that in PA6/EPR blends, clay modified with lower polarity, that is, Cloisite C15A (Montmorillonite modified with dimethyl, dehydrogenated tallow quaternary ammonium ion) and C20A, showed the most significant compatibilizing effect.…”
Section: Introductionsupporting
confidence: 57%
“…In that case, an interfacial layer around the PBS phase could act as a barrier against coalescence and induce rapid size reduction. Recently, the effects of two different organically modified MMTs, namely, C30B and a South African clay named Betsopa (BET), on the morphologies of (60/40) reactively compatibilized PLA/PBS were studied, in the context of their localization behavior …”
Section: Morphology Developmentmentioning
confidence: 99%
“…The viscoelastic behavior of PLA/PBS blends reactively compatibilized with Joncryl (J) has been extensively studied by the present authors, with two different organically modified clays (C30B and BET) being incorporated as interfacial modifiers . Initial investigations on the basis of linear rheological analyses showed that nanocomposites loaded with C30B introduced greater elasticity to the systems.…”
Section: Melt‐state Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, blending PP and LDPE is not always expected to result in improvement of the impact strength of PP owing to the immiscibility between PP and LDPE. Recently, a number of studies have shown that incorporating nanofillers and copolymers into polymer blends can improve the compatibility between blended polymers, and one such filler is montmorillonite (MMT) nanoclay. Pure MMT is incompatible with most organophilic polymers and leads to poor dispersion of silicate layers in the composites.…”
Section: Introductionmentioning
confidence: 99%